Die predikantsamp. Deel 1: Onduidelikheid oor die kerninhoud van die predikantsamp. - Burger, CW; Wepener, CJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The office of the minister. Part 1: Obscurity concerning the essence of the office of the minister. For many ministers and church members there are certain obscurities regarding the essence of the task of a minister. Nationally and internationally there are numerous changes at different levels that are responsible for this state of affairs. Therefore these changes are firstly briefly described in this article. Thereafter the deeper reasons for the vagueness concerning the office of the minister is discussed, in order to highlight some of the levels that need attention in this regard. Lastly four lines are proposed along which some clarity can be obtained. As such this article is an introduction to a series of five articles on the office of the minister and the four lines are then looked at individually in the rest of this series. It is hoped that it will help to clarify the obscurity surrounding this office with these five articles and to suggest a (new) way of looking at it within our current context.